Kaji Eksperimental Pengaruh Variasi Putaran Mesin Terhadap Laju Konsumsi Bahan Bakar Dengan Menggunakan Bahan Bakar Etanol Pada Mobil Hemat Energi Asykar Urban Etanol - Putra, Rio Ahmad Juliansyah; Aziz, Azdrizal; Mainil, Rahmat Iman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
An Energy Efficient Car vehicle is designed to be safe and efficient and energy efficient when driving, so there are several things that must be considered, including the steering system, brakes, vehicle body, vehicle weight and engine. The factor that affects performance and reduces exhaust emissions of the combustion engine is the quality of fuel combustion in the combustion chamber. One of the influencing parameters is the magnitude of the compression ratio, the ignition angle, and the use of ethanol fuel. The purpose of this study was to determine the effect of using ethanol fuel with a compression ratio of 17,1: 1 with variations in engine speed of 2000 rpm, 3000 rpm and 4000 rpm and variations in ignition angles (15o, 17o, 20o and 22o) before TMA (Upper Dead Point). After the research was carried out, the results showed that the lowest specific fuel consumption (SFC) was at 2000 rpm, namely when the ignition angle was 15o before TMA with a value of 6,236 x 10-8 with a power of 1019,8 Watts, the lowest SFC was at 3000 rpm, which is when the ignition angle is 20o before TDC with a value of 5,33 x 10-8 with a power of 1491,3 Watts, and the lowest SFC is at 4000 rpm, which is when the ignition angle is 22o before TMA with a value of 4,102 x 10-8 with a power of 2341,7 Watts. This means that the higher the engine speed, the smaller the SFC and the greater the power, the faster the time to use fuel consumption. Keywords: performance, ethanol, internal combustion engine, timing ignition